The effects of performance-monitoring technology on privacy and job autonomy. (2015) - Seppanen, Marko; Pajarre, Eila; Kuparinen, Pasi
The contemporary working environment makes good use of ICT technology development. However, since modern devices and software also enable electronic monitoring of performance, for employees the use of ICT may incur feelings of privacy invasion. This study builds a model based on the job characteristics model and the unified theory of usage and acceptance of technology (UTAUT) model explaining the relationship between willingness to adopt new ICT tools and perceived job autonomy at the level of individuals. Data from a survey of a telecom service firm with several offices were used to test the model. The findings show that the feelings of privacy invasion have a strong negative and statistically significant relationship with the perceived job autonomy.